Global longitudinal strain differentiates physiological hypertrophy from maladaptive remodeling. (June 2022) - Bewarder, Yvonne; Lauder, Lucas; Kulenthiran, Saarraaken; Schäfer, Ortwin; Ukena, Christian; Percy Marshall, Robert; Hepp, Pierre; Laufs, Ulrich; Stöbe, Stephan; Hagendorff, Andreas; Böhm, Michael; Mahfoud, Felix; et al.
Abstract: Aims: Differentiation of left ventricular (LV) hypertrophy in healthy athletes from pathological LV hypertrophy in heart disease is often difficult. We explored whether extended echocardiographic measurements such as E/e' and global longitudinal strain (GLS) distinguish physiologic from maladaptive hypertrophy in hypertrophic cardiomyopathy, excessively trained athletes' hearts and normal hearts. Methods: Seventy-eight professional athletes (cyclists n = 37, soccer players n = 29, handball players n = 21) were compared with patients (n = 88) with pathological LV hypertrophy (hypertrophic obstructive cardiomyopathy (HOCM, n = 17), hypertensive heart disease (HHD, n = 36), severe aortic valve stenosis (AVS, n = 35) and with sedentary healthy individuals as controls (n = 37). Results: LV ejection fraction (LVEF) was ≥50% in all patients, athletes (median age 26 years, all male) and the controls (97% male, median age 32 years). LV mass index (LVMI) and septal wall thickness was in normal range in controls, but elevated in cyclists and patients with pathological hypertrophy (p < 0.001 for both). E/e' was elevated in all patients with maladaptive hypertrophy but normal in controls and athletes (p < 0.001 vs. pathological hypertrophy). Furthermore GLS was reduced in patients with pathological hypertrophy compared with athletes and controls (for both p < 0.001). In subjects with septal wall thickness >11 mm, GLS (≥−18%) has a specificity of 79% to distinguish between physiological and pathological hypertrophy. Conclusion: GLS and E/e' are reliable parameters unlike left ventricular mass or LV ejection fraction to distinguish pathological and physiological hypertrophy.